The Effect of Sex on Active and Latent Tuberculosis Occurrence Based on Mannose-Binding Lectin 2 Gene Expression and Mannose-binding Lectin Plasma Concentration in Indonesia - Yanti Leman; Muhammad Nasrum Massi; Peter Kabo; Ahyar Ahmad; Nur Ahmad Tabri; Agussalim Bukhari; Siti Rafiah; Irawaty Djaharuddin; Rahmawati Minhajat; Ilhamjaya Patellongi; Ni Nyoman Sri Budayanti; Najdah Hidayah; et al. (International Journal of Mycobacteriology)
Background: Studies on the role of mannose-binding lectin 2 (MBL2) in individuals infected with tuberculosis (TB) remain limited. This study aimed to compare MBL2 gene expression and protein concentration between active and latent TB cases and to assess the influence of sex on these differences. Methods: This cross-sectional study involved 39 newly diagnosed active pulmonary TB patients and 25 individuals with latent TB who were household contacts. MBL2 gene expression was evaluated using a relative quantitative polymerase chain reaction method. MBL protein levels were measured using the enzyme-linked immunosorbent assay. Results: Among female participants, MBL2 gene expression was significantly lower in those with active TB compared to those with latent TB (P = 0.02). In male participants, no significant difference was observed (P = 0.333). Similarly, MBL protein levels tended to be lower in females with active TB than in those with latent TB, though this difference was not statistically significant (median [range]: 124.78 [65.62–499.79] vs. 208.49 [99.85–498.65] ng/mL, P = 0.099). In males, no significant difference in MBL protein levels was detected between the active TB and latent TB groups (206.86 [59.11–526.77] vs. 143.55 [65.85–290.7] ng/mL, P = 0.285). Conclusion: This study highlights the influence of sex on the expression of the MBL2 gene and plasma protein levels in TB patients. A lower expression of the MBL2 gene in active TB cases compared to latent TB cases was observed exclusively in women.